"Dobro najwyższe" w kontekście nieetycznego zarządzania organizacją przez przedsiębiorców : próba identyfikacji i diagnozy - Nogalski, Bogdan; Śniadecki, Janusz ("The Greatest Good" in the Context of Unethical Organizational Management by Entrepreneurs - an Attempt of Identification and Diagnosis, 2009)
The paper presents important social needs among which there are those requiring all market participant to adhere to basic ethical rules in the widely understood Polish business environment. The discussed subject should give proof that the basic foundation of the rules should involve pro-ethical organization management, including a "nation" type organization, which should be based on legal, moral and social norms aimed at selfless promotion of positive actions. in the creation of a pro-ethical organizational image a special role is foreseen for the entrepreneurs managing the organizations. The main objective of this paper is the analysis and evaluation of the influence of a "positive action", as the ethically highest obtainable value, on organization management by the entrepreneurs in specific areas with structural unemployment as opposed to areas free from structural unemployment. The determination whether a "positive action" in the organizations managed by the entrepreneurs is an unquestionable ethical value or rather a result of certain limiting factors is a viable question in the management of any organization.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 42, s. 38-47